THOMAS L. CHARLTON, LOIS E. MYERS, and REBECCA SHARPLESS, Eds. Thinking About Oral History: Theories and Applications - Forcier Holloway, Caroline (Archivaria, 2010)
Thinking About Oral History: Theories and Applications. THOMAS L. CHARLTON, LOIS E. MYERS, and REBECCA SHARPLESS, eds. Lanham: AltaMira Press, 2008. 392 p. ISBN-13: 978-0-7591-1090-8.